Arthroscopic repair of recurrent posterior shoulder subluxation after total shoulder arthroplasty: A case report - Grieshaber-Bouyer, Ricardo; Gerber, Christian (Journal of Bone and Joint Surgery / Case Connector, 2017)
Case: A 53-year-old man presented with osteoarthritis (Walch biconcave [B2] glenoid retroversion, 22° glenohumeral subluxation index, 65%) and a partial rupture of the supraspinatus tendon in the left shoulder. Following anatomic total joint replacement, he developed disabling recurrent posterior subluxation despite a stable prosthesis and a correctly centered glenoid head, as observed with postoperative radiography and computed tomography. In order to avoid bone loss and the complications associated with revision arthroplasty, we performed arthroscopic reefing of the posterior capsule as an experimental minimally invasive treatment. The reduction in capsular volume successfully stabilized the shoulder for approximately 9 years; thereafter, the recurrence of instability ultimately required the conversion to a reverse prosthesis. Conclusion: Arthroscopic capsular reefing proved to be an effective treatment for posterior shoulder subluxations after total shoulder arthroplasty, and can be considered to avoid revision arthroplasty in young patients with a stable and correctly centered prosthesis.
CRIS-Team Scopus Importer:2023-10-02